Mathematical optimization and economic theory - Intriligator, Michael D. 1938- (Classics in applied mathematics, 2002)
This text provides a self-contained introduction to and survey of mathematical programming and control techniques and their applications to static and dynamic problems in economics, respectively. It shows the unity of the various approaches to solving problems of constrained optimization.